Bat species composition and abundance in two underground hibernaculae in Vilnius before and after fencing - Baranauskas, Kazimieras (2006)
Species composition and abundance of hibernating bats were investigated in Šeškinė bunkers and the Paneriai tunnel in Vilnius (Lithuania). Before fencing the Šeškinė hibernaculum against human disturbance, Barbastelle Bat (Barbastella barbastellus) was abundant but Daubenton's Bat (Myotis daubentonii) was rare. After blocking the Šeškinė bunkers their microclimate changed and Barbastelle Bats disappeared, but the number of Daubenton's Bats increased. In the Paneriai tunnel, the microclimate changed insignificantly because of incomplete fencing. This resulted only in minor changes in the behaviour of bats, i.e. the numbers of both dominating bat species, Daubenton's Bat and Pond Bat, continued growing. In addition, a new bat species, Brandt Bat (Myotis brandtii), was found in the Paneriai tunnel after fencing. Blocking of entrances to bat hibernaculae can change the microclimate in them. Therefore actions meant to close the entrances should be carried out with caution, because these activities can change the species composition and/or abundance of hibernating bats.